211 Epidemiology of injury and retirement from sport among former international athletes. (3rd March 2020) - Cooper, Dale; Batt, Mark; Palmer, Debbie
Abstract : Background: High-level athletes are at an increased injury risk. Yet relatively little is known about the prevalence of career-ending injuries in high-level sport. Objective: To determine in retired international athletes: (1) the prevalence of significant injury and early retirement, and (2) if those with generalised joint hypermobility (GJH) are more likely to sustain a significant injury. Design: Cross-sectional study. Setting: Data from a survey of retired Olympic athletes. Patients (or Participants): 605 retired athletes, aged 40–97 years, 40% female ( n =244) who had competed internationally for Great Britain at the Summer and/or Winter Olympic Games. Interventions (or assessment of risk factors): Data collected on reasons for retirement from competitive sport including the type and location of significant injury. A validated line drawing instrument was used to measure generalised joint hypermobility (GJH) (Beighton >3/9). Main outcome measurements: Injury-forced retirement from a competitive sports career. Results: Of those who replied to the questionnaire (n=714), 84.7% (n=605) were retired from sport, and 21.8% (n=132) of those retired from sport reported that they had retired early because of injury. The main locations of injuries that were reported to be responsible for retirement from sport were the lower back (25.8%), knee (25.0%), lower leg (8.3%), ankle (7.6%), Achilles tendon (6.8%), shoulder (6.8%), hip (5.3%), and thigh (5.3%). The main types of injury reported to be responsible for early retirement from sport were soft tissue related (23.9%), injuries to the intervertebral disc (19.0%), intervertebral joint (18.2%), and cartilage injuries at the hip and knee (9.1%). Overall, GJH was not associated with a significant injury in female [OR 1.25; 95% CI, 0.62–2.50] or male athletes [OR 0.76; 95% CI, 0.35–1.65]. Conclusions: Injury is a major cause of early retirement among high-level athletes. However, those with GJH were no more likely to sustain a significant injury.